Source of environmental data and warming tolerance estimation in six species of North American larval anurans. (August 2018) - Katzenberger, Marco; Hammond, John; Tejedo, Miguel; Relyea, Rick
Abstract: The current global warming scenario has led to a renewed interest in determining which species are more vulnerable to climate change. Hence, it is important to understand which factors can affect estimates of species vulnerability. We determined the critical thermal maxima (CTmax ) for six species of North American anuran larvae and measured the environmental temperatures to which they are exposed during their aquatic stage to estimate their warming tolerance (WT; difference between the critical thermal maximum and the macro- and microhabitat maximum environmental temperatures). Our results indicate that these species exhibited CTmax values (37.8–41.7 °C) that were similar to other temperate species and positively correlated only with environmental temperatures measured at the microclimate scale. This indicates that microclimatic variables are better predictors of CTmax variation than macroclimate data. Moreover, most of the CTmax variation found was associated with higher taxonomic levels, indicating that related species may show similar CTmax values due to phylogenetic inertia. Studied species also exhibited high values of WT (10.3–22.6 °C), similar to temperate amphibian species from other bioregions. This indicates that there is a considerable gap between the species' critical thermal maximum and maximum environmental temperature, whether using datalogger (microclimate) or WorldClim (macroclimate) environmental data. However, WT estimates based on datalogger data were not related to those based on macroclimate environmental data. Finally, variation associated with the type of environmental data used (macro- vs. microclimate) had a profound influence on WT estimates. Hence, our perception of which species are more vulnerable to global warming changes may depend on the scale of the climate data used. Highlights: Microclimatic variables are better predictors of upper thermal limit variation. Temperate North American tadpoles present high warming tolerance. Micro- and macrohabitat data provide different estimates of warming tolerance.